Date and their processing byproducts as substrates for bioactive compounds production - Tang,Zhen-Xing (2014)
Date is the most popular fruit in middle-east countries. However, the date production process is accompanied by a substantial increase of loss during picking, storage, commercialization and conditioning process. Date and their byproducts have many essential elements for the growth of microorganisms. Thus, they can be converted into value-added compounds through biotechnology. In this paper, date and their processing byproducts used as substrates for producing value-added products such as organic acids, exopolysaccharide, antibiotics, date flavored probiotic fermented dairy, bakery yeast, etc, were reviewed.